Pineal gland volume loss in females with multiple sclerosis - Miloš Vuković; Miloš Vuković; Igor Nosek; Igor Nosek; Jasmina Boban; Jasmina Boban; Duško Kozić; Duško Kozić (Frontiers Media S.A., 2024)
IntroductionMultiple sclerosis has a complex pathophysiology, and numerous risk factors can contribute to its development, like exposure to sunlight that is associated with serum levels of melatonin. The aim of this study was to determine whether the volume of the pineal gland, assessed by magnetic resonance imaging (MRI), correlated with the presence of multiple sclerosis.MethodsThis retrospective study included a total of 394 patients. Subjects were divided into two groups: the first group consisted of 188 patients with a definite diagnosis of multiple sclerosis (based on revised McDonald criteria) and the second group consisted of 206 healthy controls. To examine the influence of age on pineal gland volume, we stratified the whole sample into three age groups: first involved patients under 20 years, second patients between 20 and 40 years, and third group included patients over 40 years. The maximum length (L) and height (H) of the pineal gland were measured on the T1-weighted sagittal images, and the width (W) was measured on the T2-weighted coronal or axial images. The volume of the gland was calculated as an approximation to an ellipse, according to the formula V = (L × H × W)/2.ResultsPineal gland volume of female multiple sclerosis (MS) patients (N = 129) was significantly lower than in healthy females (N = 123) (p = 0.013; p < 0.05), unlike in males where there is not such difference. Also, pineal gland volume is not age-dependent, and the observed smaller pineal gland in MS patients can reliably be attributed to the disease itself. Additionally, large pineal gland size, especially over 62.83 mm3 when compared to pineal gland volume below 31.85 mm3 is associated with more than double reduced risk of multiple sclerosis (OR 0.42; p = 0.003).DiscussionOur results suggest that women with multiple sclerosis have smaller pineal glands that can theoretically be explained by a lack of input stimuli and the resultant decrease in gland volume. Additionally, the risk of multiple sclerosis is reduced in larger pineal gland volumes.